Brassinosteroids function in spikelet differentiation and degeneration in rice. Issue 8 (1st January 2019) - Zhang, Weiyang; Zhu, Kuanyu; Wang, Zhiqin; Zhang, Hao; Gu, Junfei; Liu, Lijun; Yang, Jianchang; Zhang, Jianhua
Abstract: Brassinosteroids (BRs) play crucial roles in many aspects of plant development. However, their function in spikelet differentiation and degeneration in rice ( Oryza sativa L.) remains unclear. Here, we investigated the roles of these phytohormones in spikelet development in field‐grown rice subjected to five different nitrogen (N) fertilization treatments during panicle differentiation. BR levels and expression of genes involved in BR biosynthesis and signal transduction were measured in spikelets. Pollen fertility and the number of differentiated spikelets were closely associated with 24‐epicastasterone (24‐epiCS) and 28‐homobrassinolide (28‐homoBL) levels in spikelets. Enhanced BR biosynthesis and signal transduction, in response to N treatment, enhanced spikelet differentiation, reduced spikelet degeneration, and increased grain yield. Increases in proton‐pumping ATPase activity, ATP concentration, energy charge, and antioxidant system (AOS) levels were consistent with 24‐epiCS and 28‐homoBL concentrations. Exogenous application of 24‐epiCS or 28‐homoBL on young panicles induced a marked increase in endogenous 24‐epiCS or 28‐homoBL levels, energy charge, AOS levels, spikelet differentiation, and panicle weight. The opposite effects were observed following treatment with a BR biosynthesis inhibitor. Our findings indicate that, in rice, BRs mediate the effects of N fertilization on spikelet development and play a role in promoting spikelet development through increasing AOS levels and energy charge during panicle development. Abstract : Brassinosteroids mediate the effect of nitrogen fertilization on spikelet development, and play vital roles in promoting spikelet differentiation and reducing spikelet degeneration through increasing levels of antioxidant system and energy charge during panicle development in rice ( Oryza sativa L.).